Single dish gradient screening of small molecule localization. Issue 35 (17th August 2016) - Beuzer, Paolo; Axelrod, Joshua; Trzoss, Lynnie; Fenical, Willam; Dasari, Ramesh; Evidente, Antonio; Kornienko, Alexander; Cang, Hu; La Clair, James J.
Abstract : Understanding trafficking in cells and tissues is one of the most critical steps in exploring the mechanisms and modes of action (MOAs) of a small molecule. Abstract : Understanding trafficking in cells and tissues is one of the most critical steps in exploring the mechanisms and modes of action (MOAs) of a small molecule. Typically, deciphering the role of concentration presents one of the most difficult challenges associated with this task. Herein, we present a practical solution to this problem by developing concentration gradients within single dishes of cells. We demonstrate the method by evaluating fluorescently-labelled probes developed from two classes of natural products that have been identified as potential anti-cancer leads by STORM super-resolution microscopy.